Strehl Ratio and Myopia in Chinese Adolescents: The Tuyou County Pediatric Eye (TYPE) Study - Bian, Xiaoyan (Int J Gen Med, 2021)
AIM: To investigate the relationships between property of the visual quality, Strehl ratio (SR) and the degree of myopia. METHODS: A total of 444 anatomically normal eyes of 222 adolescents were enrolled in the TYPE study. Based on spherical equivalent (SE), subjects were divided into four groups: emmetropia/control (SE: +0.75 to −0.75 D), low myopia (SE: −0.75 to −3.00D), moderate myopia (SE: −3.00 to −5.00D), high myopia (SE: <−5.00D). Axial length (AL) was measured. SR was attained with an OPD-III SCAN and calculated under a 3 mm pupil diameter. RESULTS: The overall SR (mean ± SD) was 0.40 ± 0.08. Among all included eyes, the SR in eyes with the emmetropia, low myopia, moderate myopia and high myopia was 0.80 ± 0.11, 0.31 ± 0.04, 0.21 ± 0.11, and 0.11 ± 0.02, respectively. Furthermore, the K2 in eyes with the emmetropia, low myopia, moderate myopia and high myopia was 43.83±1.50, 43.96±1.37, 43.4±5.52, and 45.16±1.43, respectively. Significant differences were detected within the four groups in terms of SR and K2 (P < 0.001). Multiple regression analysis confirmed that AL negatively affected SR independently (P < 0.001). CONCLUSION: Our findings provide a useful basis for the conclusion that myopia affects visual quality SR in Chinese adolescents. Besides, when performing visual quality SR, axial length must be taken into consideration, as it will influence SR.